Pengaruh Promosi Harbolnas, Influencer, dan Gaya Hidup terhadap Pembelian Spontan dengan Religiusitas sebagai Variabel Moderasi - Pramesti Zinmi, Anna; Safitri, Junaidi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of National Online Shopping Day (Harbolnas) promotions, influencers, and shopping lifestyle on spontaneous online purchasing behavior, as well as to examine the role of religiosity as a moderating variable in these relationships. A quantitative approach was employed using a survey method through the distribution of questionnaires to 112 student respondents from the Faculty of Islamic Studies at the Islamic University of Indonesia. The data were analyzed using multiple linear regression and moderated regression analysis (MRA) with the assistance of SPSS version 25. The findings reveal that Harbolnas promotions, influencers, and shopping lifestyle have a positive and significant effect on spontaneous online purchasing behavior. Among these variables, shopping lifestyle is the most dominant factor influencing impulsive behavior. Additionally, religiosity shows a negative and significant moderating effect, indicating that a high level of religiosity weakens the influence of shopping lifestyle on impulsive purchases. This suggests that religious values serve as an effective internal control mechanism in limiting consumer impulsivity among students in the digital era. This study contributes theoretically to the development of value-based digital consumer behavior models and offers practical implications for industry stakeholders and educational institutions to foster more ethical and mindful consumer behavior.